Dosežki in izzivi pri graditvi gozdnih prometnic v Sloveniji - Robek, Robert (Gozdarski vestnik, 2006)
The intensification of wood harvesting in Slovenian forests will require further investments into traffic way construction and reconstruction. After a decade of regression in forest engineering a distinct increase in skidding trail construction and intentional revival of road constructions in state forests have occurred since the year 2000. On the basis of the project documentation review and monitoring of four road construction examples recent novelties and trends in forest traffic way construction are described. Major professional achievements are improved operational road planning procedures and integration of forest traffic ways into relevant national legislation. Themain barriers related to forestry infrastructure projects are capital weaknesses, short term orientation and poor cooperativeness of private forest owners. In the future we shall have to introduce and assert rational technicalprocedures as well as harmonize the legislative frame with financial measures to encourage forest owners to better cooperation, long-term oriented investments and complex technological solutions. The key elements for achieving such goals are high quality forestry professionals who possess the knowledge and will to limit infrastructure investment initiatives with sustainable long term forestry management goals.
Keywords: gozdne ceste; vlaka; forestry; gozdarstvo; zakonodaja; Slovenia; Slovenija